2006
DOI: 10.1111/j.1365-2966.2006.10002.x
|View full text |Cite
|
Sign up to set email alerts
|

H  kinematics of the SINGS nearby galaxies survey -- I

Abstract: This is the first part of an Hα kinematics follow‐up survey of the Spitzer Infrared Nearby Galaxies Survey (SINGS) sample. The data for 28 galaxies are presented. The observations were done on three different telescopes with Fabry–Perot of New Technology for the Observatoire du mont Megantic (FaNTOmM), an integral field photon‐counting spectrometer, installed in the respective focal reducer of each telescope. The data reduction was done through a newly built pipeline with the aim of producing the most homogeno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(151 citation statements)
references
References 60 publications
10
139
1
1
Order By: Relevance
“…This is a good compromise between the different values reported in the literature ranging from D = 16.8 Mpc (Tully & Fisher 1988) to D = 22.6 Mpc (LEDA, 2006). Similarly to GB05 we will initially assume that the inclination angle and the position angle of NGC 4579's disk are i = 36 • and PA = 95 • , respectively, in rough agreement with previous determinations based on kinematical model fitting (e.g., Rubin et al 1999;Koopmann et al 2001;Daigle et al 2006) and photometric model fitting (e.g., Young & Currie 1998;Paturel et al 2000). These parameters will be further discussed in Sect.…”
Section: Aims Of This Papermentioning
confidence: 64%
“…This is a good compromise between the different values reported in the literature ranging from D = 16.8 Mpc (Tully & Fisher 1988) to D = 22.6 Mpc (LEDA, 2006). Similarly to GB05 we will initially assume that the inclination angle and the position angle of NGC 4579's disk are i = 36 • and PA = 95 • , respectively, in rough agreement with previous determinations based on kinematical model fitting (e.g., Rubin et al 1999;Koopmann et al 2001;Daigle et al 2006) and photometric model fitting (e.g., Young & Currie 1998;Paturel et al 2000). These parameters will be further discussed in Sect.…”
Section: Aims Of This Papermentioning
confidence: 64%
“…They confirm what Roberts (1969) had predicted theoretically: variations of 10 − 30 km s −1 in the velocity are found when the gas crosses the density wave. Bar-induced non-circular motions have also been analysed in the literature, and the first Garrido et al 2002 (GHASP), Daigle et al 2006a (SINGS sample) and Chemin et al 2006 (VIRGO sample), shown along with the characteristics of the data used in this paper. Note) The '-' denotes that there are no galaxies with that criteria (VIRGO, GHASP and this paper), or that no information about the seeing was presented (SINGS).…”
Section: Non-circular Motionsmentioning
confidence: 99%
“…In the Introduction, we mentioned the Hα FP kinematic surveys of Garrido et al 2002 (GHASP), Daigle et al 2006a (SINGS sample) and Chemin et al 2006 (VIRGO sample). These surveys have used instrumentation similar to GHαFaS: Cigale and FaNTOmM (FabryPerot de Nouvelle Technologie de l'Observatoire du Mont Mégantic 3 ).…”
Section: Comparison With Literature Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The agreement is within 20%, except where the CO flux approaches the detection limit of the BIMA SONG survey (R > ∼ 2 kpc). One advantage of applying Gaussian fits is that we can get better covering maps if we use a Hanning smoothing algorithm in the spectral direction before fitting the individual Gaussian profiles (e.g., Hernandez et al 2005;Daigle et al 2006). This procedure does not affect the line amplitude or shift.…”
Section: Molecular Gasmentioning
confidence: 99%